Risk Factor of Central Lymph Node Metastasis in Papillary Thyroid Microcarcinoma - Rizwan Abdul Salam, Farhana, Munawer Latif Memon, Ambreen Zafar, Nazia Siddique, Shahida Mushtaq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: This study's goals were to assess the cervical central lymph node status and predictive value of SLN biopsy during operate and to identify clinic pathological factors, that were used to be independent predictors for analyzed central lymph node metastasis in papillary thyroid carcinoma. Study design: This was a cross-sectional study conducted at Sahara Medical College, Narowal for the duration of six months, from July 2022 to December 2022. Methods: The total N=300 people participated in this study. The participants were split into two groups: positive for cervical central lymph nodes CCLN (n = 210) and negative for cervical central lymph nodes CCLN (n = 90). In cases with positive SLNB, the positive sentinel lymph node ratio and additional positive lymph node (APLN) were examined. Investigators looked into SLNB's effectiveness. Results: The age range was 24-40 years in which cervical central lymph node case was (57%); p=0.002**. The maximum diameter of tumor (98%) was 3-4 cm show significantly P<0.05. The multiple focus included unilateral (18.3%) and bilateral region (82%) show significant changes P<0.05. According to the tumor locations, the positive case of central lymph node were as following; lower area (20%), middle area (53.3%) and upper area (27%) the difference were significant (p<0.05). The metastatic rate of lymph node was related to SLN (67%) and CCLNM (46%). APLN positive show additional lymph node on cancerous participants. The evaluation of CNM and APLN using the sensitivity, specificity, false positive rates, positive predictive value, and negative predictive value of SLNB. Conclusion: In participants with positive case reports, age, sex, tumour size, location, extra thyroidal invasion, and capsule involvement were independent risk factors for CLN metastasis. If a positive SLN could be used to predict the presence of APLN, a theoretical basis for intraoperative lymph node dissection might be offered. Keyword: Metastasis, Tumor size, Multifocality,